Development of a Mini Crane for Lightweight Lifting Applications - Syamel Akmal Ahmad Kamal; Nur Aini Sabrin Manssor; Nurrul Amilin Zainal Abidin; Nurrul Hanna Mas’aud (Journal of Advanced Mechanical Engineering Applications, 2026)
Conventional cranes are often bulky and difficult to be operated in confined spaces, thus the demand for a more compact and safe lifting solution is rising. The main objectives of this study are to design, analyze, and fabricate a portable compact crane to improve safety and easy to be operated. The crane was first conceptually designed and modeled using SolidWorks 2021 and the structural performance was then evaluated through finite element simulation to determine the stress distribution, displacement, and strain under maximum operating load. The results showed that the maximum stress, displacement, and strain fall within the acceptable limits of mild steel. A prototype was then fabricated using standard manufacturing processes, such as cutting, drilling, welding, and mechanical fastening, before undergoing performance testing. The test demonstrated that the mini crane was able to lift and lower up to 188 kg loads with a maximum lifting height of 1700 mm and an adjustable reach between 1200 mm and 1400 mm. Overall, the mini crane offers a practical and affordable lifting solution for restrictive environments, thus improving safety and mobility compared to conventional cranes.